A “Lockdown” of Materialism Values and Pro-Environmental Behavior: Short-Term Effects of the COVID-19 Pandemic - Jana Sophie Kesenheimer (MDPI AG, 2021)
The COVID-19 pandemic led to serious restrictions on peoples’ everyday lives and had severe economic impacts. In contrast, “lockdown” restrictions led to short-term beneficial effects for the environment. In the present study, we compared pro-environmental behavior and materialism values before, during, and after COVID-19 lockdown restrictions in the spring of 2020. The results of an online study using 370 participants showed a decrease in materialism values and pro-environmental sacrificing actions. In contrast, ecologically compatible actions decreased during the lockdown and increased again to the initial level after restrictions were loosened. Moreover, pro-environmental attitudes had a diminishing effect on materialism values, especially during lockdown restrictions. Agreeableness had a diminishing effect on materialism values during the lockdown. In contrast, trait narcissism enhanced materialism values, which were strongest after the lockdown was over. In conclusion, materialism values and pro-environmental behaviors were “locked down” due to COVID-19 restrictions but did not show the expected rebound effects. Practical and theoretical implications are discussed.